THE IMPACT OF PROPERTY LAYER ON SOCIO-ECONOMIC DEVELOPMENT IN CIVIL DEVELOPMENT - Shaymanova Adiba Ergashevna, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
Our country's purpose when it earned independence was to establish a free, democratic legal state and civil society. Radical reforms are being pursued as part of the process of reaching this goal, with the purpose of steadily strengthening and increasing the role and number of property owners in society. The Republic of Uzbekistan's experience shows that the layer of owners, which consists of representatives from various social groups, mental and physical labor, forms the social basis of civil society's socioeconomic development, and is a reliable source of driving force and stability for the country's development. Opinions and views on the impact of the property layer on socioeconomic growth will be presented in this article.